Optimized Conformal Total Body Irradiation methods with Helical TomoTherapy and Elekta VMAT: Implementation, Imaging, Planning and Dose Delivery for Pediatric Patients - Loginova, Anna Anzorovna; Tovmasian, Diana Anatolievna; Lisovskaya, Anastasiya Olegovna; Kobyzeva, Daria Alexeevna; Maschan, Michael Alexandrovich; Chernyaev, Alexander Petrovich; Egorov, Oleg Borisovich; Nechesnyuk, Alexey Vladimirovich (Frontiers in Oncology, 2022)
Optimized conformal total body irradiation (OC-TBI) is a highly conformal image guided method for irradiating the whole human body while sparing the selected organs at risk (OARs) (lungs, kidneys, lens). This study investigated the safety and feasibility of pediatric OC-TBI with the helical TomoTherapy (TomoTherapy) and volumetric modulated arc (VMAT) modalities and their implementation in routine clinical practice. This is the first study comparing the TomoTherapy and VMAT modalities in terms of treatment planning, dose delivery accuracy and toxicity for OC-TBI in a single-center setting. The OC-TBI method with standardized dosimetric criteria was developed and implemented with TomoTherapy. The same OC-TBI approach was applied for VMAT. Standardized treatment steps, including positioning and immobilization, contouring, treatment planning strategy, plan evaluation, quality assurance, visualization and treatment delivery procedure were implemented for 157 patients treated with TomoTherapy and 52 patients treated with VMAT. Both modalities showed acceptable quality of the planned target volume dose coverage with simultaneous OARs sparing. The homogeneity of target irradiation was superior for TomoTherapy. Overall assessment of the OC-TBI dose delivery was performed for 30 patients treated with VMAT and 30 patients treated with TomoTherapy. The planned and delivered (sum of doses for all fractions) doses were compared for the two modalities in groups of patients with different heights. The near maximum dose values of the lungs and kidneys showed the most significant variation between the planned and delivered doses for both modalities. Differences in the patient size did not result in statistically significant differences for most of the investigated parameters in either the TomoTherapy or VMAT modality. TomoTherapy-based OC-TBI showed lower variations between planned and delivered doses, was less time-consuming and was easier to implement in routine practice than VMAT. We did not observe significant differences in acute and subacute toxicity between TomoTherapy and VMAT groups. The late toxicity from kidneys and lungs was not found during the 2.3 years follow up period. The study demonstrates that both modalities are feasible, safe and show acceptable toxicity. The standardized approaches allowed us to implement pediatric OC-TBI in routine clinical practice.